Fractionation and identification of the nucleic acid-related substances secreted by Streptomyces aureofaciens - De Carvalho, Alírio [UNESP]; Malavolta, Cristina Marques [UNESP]; Quirino, Gustavo Hoff [UNESP]; Fernandes, José Atanasio Dos Santos [UNESP]; Mengatti, Jair [UNESP]; Contiero, Jonas [UNESP]; Oppermann, Heloísa Ribi [UNESP]; Molinari, Rubens [UNESP] (My University, 1996)
S. aureofaciens growth in a chemically defined medium was associated with the active secretion of nucleic acid-related substances in the medium. High secretion depended on low availability of phosphate, and fractionation showed 7 anionic substances were secreted as major components. When compared to 76 known purine and pyrimidine derivatives only orotic acid was identified. Cationic components are among the minor concentration components secreted which have been identified as cytosine, inosine, cytidine, adenine, guanine and, probably, 1-methyl-adenine.
Keywords: Fractionation and identification; Nitrogenous bases; Nucleic acid-related substances; Nucleosides; Streptomyces aureofaciens